The Method of Miniaturization of a Microstrip Branch-Line Couplers - D. A. Letavin (Известия высших учебных заведений России: Радиоэлектроника, 2017)
Traditional microstrip coupler devices have found various applications in radio engineering. They can be used in radiolocation, radio  navigation, communications, antenna systems, radio measurements  and other fields of technology. They are also used as a functional  node fo r building power dividers, mixers, modulators, power  summators, and beamforming elements. The design of the branch- line coupler consists of segments of microstrip lines with phase shifts of 90 degrees. However, the dimensions of such devices can be  impractical, especially at low frequencies. Therefore, it is necessary  to use various design solutions aimed at reducing the size of the  device, while maintaining its characteristics at the level of a standard device. In order to eliminate parasitic transmission bands, reduce  overall dimensions and economical manufacture, electrodynamic  structures (ESs) that function as quarter-wave segments will be introduced into the design topology, and their dimensions are much shorter in length, and they can be manufactured by standard etching technology of printed circuit boards. The shape of the ES is chosen  to maximize the use of free space within the coupler, without  crossing adjacent conductor lines. The thickness of the microstrip  lines and the gaps between them are selected in terms of  technological feasibility. To take into account the influence of  neighboring conductive lines on each other and other factors, the AWR DE 13 program was used. The compact design has the following dimensions 15.4 * 16.4 = 252.6 mm2, which is 75.7 %  less than the conventional design. Based on the simulation results, a prototype of a compact coupler was manufactured. Measurements of its parameters were carried out using the vector network analyzer Rohde & Schwarz ZVA 24 and the calibration kit K52. As a result, a  compact design was obtained, easy to manufacture, which can find a variety o f applications in microwave technology. Further reduction in size is possible due to the use of higher resistance lines and a reduction in the gap between them. However, further reduction will lead to a greater decrease in the bandwidth of operating frequencies, and the characteristics obtained will increasingly differ from those of the original design.